2017
DOI: 10.1111/jdv.14542
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of sonidegib in patients with locally advanced and metastatic basal cell carcinoma: 30‐month analysis of the randomized phase 2 BOLT study

Abstract: BackgroundPatients with locally advanced basal cell carcinoma (laBCC) or metastatic BCC (mBCC), two difficult‐to‐treat populations, have had limited treatment options. Sonidegib, a hedgehog pathway inhibitor (HPI), was approved in laBCC based on results from the BOLT trial.ObjectiveTo evaluate long‐term efficacy and safety of sonidegib in laBCC and mBCC in the BOLT 18‐ and 30‐month analyses.MethodsBOLT (NCT01327053, ClinicalTrials.gov), a double‐blind phase 2 study, enrolled patients from July 2011 until Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 31 publications
10
192
0
8
Order By: Relevance
“…Additionally, disease control rate remained unchanged between 30 and 12 months at a value of 92.3% for the 200 mg arm and 91.3% for the 800 mg arm per central review. Per central review at 30 months, the estimated median DOR for the 200 mg arm was 24.0 months; for the 800 mg arm, the Data taken from [14][15][16].…”
Section: -Month Follow-upmentioning
confidence: 99%
“…Additionally, disease control rate remained unchanged between 30 and 12 months at a value of 92.3% for the 200 mg arm and 91.3% for the 800 mg arm per central review. Per central review at 30 months, the estimated median DOR for the 200 mg arm was 24.0 months; for the 800 mg arm, the Data taken from [14][15][16].…”
Section: -Month Follow-upmentioning
confidence: 99%
“…It should be noted that no cases of rhabdomyolysis (defined as creatine kinase elevations >10-fold higher than the pretreatment or baseline level [or >10 times the upper limit of the normal range if no baseline level was reported] in conjunction with a 1.5-fold increase from baseline in serum creatinine) were confirmed by an independent safety review committee composed of experts on muscle toxicity [23]. With 30 months of data, sonidegib showed a similar AE profile to that seen at 18 months [11,23].…”
Section: Sonidegib: Qol Data From the Bolt Trialmentioning
confidence: 86%
“…In the ERIVANCE trial at 30 months, patients with laBCC or mBCC showed investigator-assessed objective response rates of 60.3% and 48.5%, respectively [10]. In the BOLT study, patients treated with sonidegib at 30 months showed objective response rates of 71.2% for laBCC and 23.1% for mBCC (per investigator review) [11]. Because advanced BCC is associated with sun exposure, it occurs often on visible parts of the body, such as the face, ears, and neck [12].…”
Section: Introductionmentioning
confidence: 99%
“…HPIs offer a therapeutic option of considerable efficacy for patients with difficult‐to‐treat inoperable or recurrent locally advanced and metastatic basal cell carcinoma by inhibiting SMO of the Hh pathway and the downstream inhibition of the transcription of target genes implicated in BCC development and differentiation . Investigator‐assessed response rates were 60.3% for laBCC and 48.5% for mBCC with vismodegib and 71.2% for laBCC with sonidegib . Given the rarity of mBCC (<0.1%) 1 , there are only limited reports of chemotherapy for patients with mBCC with transient or disappointing results or intolerable toxicity .…”
Section: Meeting the Needs Of Advanced Bcc: Treatment With Hedgehog Imentioning
confidence: 99%
“…Given the rarity of mBCC (<0.1%) 1 , there are only limited reports of chemotherapy for patients with mBCC with transient or disappointing results or intolerable toxicity . For mBCC, the median progression‐free survival (PFS), with vismodegib at approved dosing, was 9.3 months in the ERIVANCE study and 13.1 months in the STEVIE study , and with sonidegib was 13.1 months in the BOLT study . As HPIs become increasingly incorporated in the clinical practice, dermatologists will face many challenges during the monitoring of treatment of patients with HPI: to optimally schedule clinical follow‐up, to assess efficacy and tumor responses, to monitor for toxicity and tolerability issues, and to inform patients about which adverse events to expect and how to effectively cope.…”
Section: Meeting the Needs Of Advanced Bcc: Treatment With Hedgehog Imentioning
confidence: 99%